PENGEMBANGAN SISTEM WHISTLEBLOWING BERBASIS WEB PADA PEMERINTAH KABUPATEN BULELENG MENGGUNAKAN METODE EXTREME PROGRAMMING - Lovyetha Evelyn Sirait; Ketut Meilan Kartika Putri; Gede Surya Mahendra (Computer Based Information System Journal, 2026)
The implementation of transparent and accountable governance requires an effective and secure reporting system for violations. However, whistleblowing mechanisms at the local government level still face obstacles, such as manual processes, low protection for whistleblowers, and inefficient handling of reports. This study aims to develop a websitebased Buleleng Whistleblowing System as a means of internal violation reporting for Civil Servants (ASN) in the Buleleng Regency Government. The study uses an applied approach with the Extreme Programming (XP) software development method. Data was collected through observation, interviews, and literature studies. The results of the study show that the developed system is capable of supporting the process of reporting, verifying, and monitoring reports in a structured, secure, and anonymous manner. The application of the XP method enables the development of a system that is responsive to user needs and supports the effectiveness of internal oversight and local government accountability